Distance Interpreting: Terminology, Taxonomy, and Key Directions of Research - E. S. Krasnopeyeva (Научный диалог, 2021)
The article presents a review of the current state of research on distance interpreting (DI), which is defined as information and communication technology-enabled interpreting. The relevance of this study is associated with the rapid development and dissemination of remote interpreting technology fuelled by the restrictions imposed during the COVID-19 pandemic. It discusses DI taxonomy and examines terminology used to refer to various DI modalities in academic and professional discourse. Names of DI services used on the websites of the major Russia’s language service providers are also discussed. The study shows that both Russian and English terminology used in the field of DI is varied and lacks stability. The article presents a short review of theoretical and methodological approaches applied in the key English-language studies of telephone interpreting, videoconference interpreting, and remote simultaneous and consecutive interpreting in different social contexts. The author pays attention to the results of a variety of studies, and describes the categories of “presence”, adaptation and multisensory integration that are essential to the interpretation of translation strategies and the nature of stress caused by DI.